Near-infrared spectroscopy in process control and quality management of fruits and wine - Jana Gehlken (Julius Kühn-Institut, 2021)
Recently, rapid quality assessment of food is an increasingly important topic. The rising demand of consumers for high quality products generates a need to establish fast and suitable analytical methods. Near-infrared (NIR) spectroscopy has turned out to be a time-saving, cheap, easy-to-use and environmentally friendly technique, which can be applied for the determination of manifold quality attributes in various kinds of food matrices. This article gives overview of the basic principles of near-infrared measurements and describes the immense field of applications, with the main focus on fruits, grapes and wine and the evaluation of wine aroma.